A profissionalidade emergente dos licenciandos em música: conhecimentos profissionais em construção no PIBID música - Nair Aparecida Rodrigues Pires (2015)
The aim of this study is to understand the emerging professionality of undergraduates that participate of the Scholarship Program for New Teachers (Pibid) in the field of Music of IES in MG, by studying its relationship with academic models applied in music teacher education. The specific objectives include characterization of frameworks for music teacher education; identification of professional knowledge built between universities and elementary schools; and analysis of signs of emerging professionality in music teachers. The theoretical basis of this study is the concept of emerging professionality coined by Jorro (2011), anchored by studies that discuss professional teacher knowledge (SHULMAN, 1986, 1987) and teacher education. The empirical research considered seven undergraduate programs in music offered in the state of Minas Gerais that developed music subprojects within the Pibid. The methodology included document reviews; 7 semi-open interviews with the Coordinator-General of Pibid and Professors in charge of subprojects in the field of music; 6 focus groups and 49 questionnaires administered to students enrolled in undergraduate programs in music, which were also part of the Scholarship Program for New Teachers (Pibid) in the field of music in the state. The qualitative research technique applied was the content analysis. By means of this study, it was possible to characterize frameworks of music teacher education applied in undergraduate programs in music offered in the state of Minas Gerais, by applying a Model for Analysis of Professional Knowledge in Music Teacher Education. The comparative analysis of music degree programs reveal a strong influence of the technical rationality model in structuring the professional knowledge, which focuses on musical language expertise, especially instrumental, in detriment of theoretical, practical and basic knowledge. The data indicate that because most models for training music teachers favor disciplinary knowledge, undergraduates tend to consider this the main knowledge in music education. This fact signals the fragility of teaching professionality in the undergraduate programs in the field of music teacher education. Through the analysis of professional knowledge in construction by undergraduates notes the presence of the seven types of knowledge domains proposed by Shulman (1987), with the emergence of the category of ethical knowledge of the reality as it is. The relationship between the structure of sub-projects and the ways music teaching is structured in elementary schools points the curriculum knowledge as an evidence of an emerging professionality.